البنى السردية وسماتها الأسلوبية في القصة الجزائرية القصيرة - بوغزالة, محمد عبد الحميد (Universty of Eloued جامعة الشهيد حمه لخضر, 2021)
الملخص: تناولت هاته الدراسة مكونات البنية السردية وسماتها الأسلوبية في نماذج من أعمال السعيد بوطاجين القصصية، وقد وقع اختياري على نصوص هذا الكاتب باعتبار أنه يُعد من أكثر الأدباء الجزائريين غزارة في كتابة القصة القصيرة مقارنة بغيره، كما أنه بقي محافظا على طابعها التقليدي. تعرضنا في هذا البحث إلى آليات الخطاب السردي، وأدبية النص السردي، وهما المكونان الرئيسان للبنية السردية في القصة القصيرة، وقبل التطرق لهما قدمت لمحة وجيزة عن القصة الجزائرية: نشأتها، مراحل تطورها، أهم موضوعاتها وسماتها الفنية. خصصنا الفصل الأول والثاني من الدراسة لآليات الخطاب السردي، حيث تناولنا في الفصل الأول بنية الزمن السردي وآلياته المتمثلة في الاستذكار والاسترجاع والتواتر والإبطاء والتسريع، والتمثيل لذلك، مع الوقوف على السمات الأسلوبية التي ميزت هذه البنية، وفي الفصل الثاني: الرؤية السردية وبنية الشخصية، ففي الرؤية السردية تطرقنا إلى أنواع الرواة ممثلين لذلك حسب رؤية جيرار جينيت وفي بنية الشخصية: أنواع الشخصيات، وأسلوبية القاص في اختيار أسماء تلك الشخصيات. أما فيما يخص أدبية النص السردي فقد شملت الفصل الثالث الذي عالجنا فيه شعرية الحوارية وجمالية التناص، حيث استعرضنا في شعرية الحوارية أشكالها المختلفة مع التمثيل لكل منها لرصد تعدد الأصوات وتداخلها واختلاف الرؤى ووجهات النظر بين ثنايا نصوص الكاتب، وفي جمالية التناص أوردنا المصادر المختلفة التي نهل منها الكاتب وعزز بها نصوصه مع الوقوف على جماليات توظيف تلك النصوص المتناصة، مع تسليط الضوء على عتبات الكتابة وجمالياتها في النتاج القصصي البوطاجيني. وخلصنا في نهاية رحلتنا البحثية مع البنية السردية في القصة الجزائرية القصيرة إلى مجموعة من النتائج أبرزها أن القصة الجزائرية القصيرة ظهرت متأخرة، وبالرغم من ذلك قفزت قفزات سريعة في تطور بنيتها الفنية، وتنويع آلياتها السردية، متجاوزة المحاولات الأولى المتعثرة، كما توصلنا إلى أن قصص بوطاجين عالجت الوضع المتردي الذي آلت إليه البلاد بأسوب ساخر لا يراد به إثارة الابتسامة المريحة الممتعة فحسب، وإنما هي مفارقة تنتقد الوضع القائم وتحث على تغييره. وأخيرا أرجو أن تفتح هذه الدراسة آفاقا جديدة للبحث وتسليط الضوء على الأعمال السردية الجزائرية التي لم تنل حضها من البحث والدراسة. Abstract: This study dealt with the components of the narrative structure and their stylistic features in examples of the stories of Said Butajin. I chose this writer’s texts as he is considered one of the most prolific Algerian writers in writing the short story compared to others, and he has preserved its traditional character. In this research, we dealt with the mechanisms of the narrative discourse and the literature of the narrative text, which are the two main components of the narrative structure in the short story. Before dealing with them, I presented a brief overview of the Algerian story: its inception, stages of development, its most important topics and artistic features. We devoted the first and second chapters of the study to the mechanisms of narrative discourse, where in the first chapter we dealt with the structure of narrative time and its mechanisms represented in recall, recall, frequency, slowing down and speeding up, and representing that, with an examination of the stylistic features that characterized this structure, and in the second chapter: the narrative vision and the structure of the personality. Narrative vision We dealt with the types of narrators, representing that according to the vision of Gérard Genet and in the structure of the character: the types of characters, and the style of the narrator in choosing the names of these characters. As for the literature of the narrative text, it included the third chapter in which we dealt with the poetry of dialogue and the aesthetic of intertextuality, where we reviewed in the poetry of dialogue its different forms with representation for each of them to monitor the multiplicity of voices and their overlap and the different visions and points of view between the folds of the writer's texts. Including the writer and enhanced his texts with an examination of the aesthetics of employing these intertwined texts, while highlighting the thresholds of writing and its aesthetics in the production of Al-Butagene fiction. At the end of our research journey with the narrative structure in the Algerian short story, we concluded a set of results, the most prominent of which is that the Algerian short story appeared late, despite this rapid leaps in the development of its artistic structure and diversification of its narrative mechanisms, surpassing the first stalled attempts, and we also concluded that the stories of Butagine I dealt with the deteriorating situation in the country in a sarcastic manner that is not only intended to provoke a comfortable and pleasant smile, but rather is a paradox that criticizes the existing situation and urges its change. 1. Finally, I hope that this study will open new horizons for research and shed light on the Algerian narrative works that have not been prompted by research and study..
دراسة في نماذج من أعمال السعيد بوطاجين
أطروحة دكتوراه تخصص أسلوبيات في الأدب العربي
Keywords: السرد، البنية السردية، القصة القصيرة، الأسلوبية; Narration, narrative structure, short story, stylistics